Implementasi Program Kemitraan dan Kewirausahaan SMK PK pada Keahlian Busana di SMK Negeri 1 Saptosari - Ely Tri Wulandari; Putu Sudira (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study aims to analyze the implementation of the Center of Excellence Vocational High School Program (SMK PK) in the Fashion Design Expertise Program at SMKN 1 Saptosari. The research employed a qualitative case study approach, using in-depth interviews, participatory observations, and documentation as data collection techniques. SMKN 1 Saptosari has been designated as an SMK PK implementer since 2021 and continues to receive program support until 2025. The study was conducted from October 2024 to February 2025, focusing on program selection strategies, planning, implementation, supporting factors, and challenges. The findings indicate that the selection strategy was carried out through school potential mapping, infrastructure strengthening, and partnership development with business and industry sectors (DUDI). Program planning was focused on developing the School Operational Curriculum (KOSP) based on the Merdeka Curriculum and tailored to the needs of the creative industry, particularly fashion. Program implementation included strengthening the Teaching Factory, developing an industry-based work culture, entrepreneurship training, and active collaboration with industry partners. Supporting factors included the availability of industry-standard practice facilities, strong school management support, and mentoring from universities and industry. Challenges remain in terms of limited industry-standard equipment, low utilization of digital technology, and the need to improve teachers’ capacity in project-based learning. Overall, the SMK PK program at SMKN 1 Saptosari has contributed positively to improving vocational education quality, although further strengthening of human resources and infrastructure is still required.